Exploring the Socio-Economic Challenges and Daily Life of Persons with Disabilities Insights from Mehendiganj Upazila: A Case Study Approach - Hamid, Abdul; Parvin, Laboni; Ahmed, Syed Tanim; Akter, Sinthya (Journal of Knowledge Learning and Science Technology ISSN: 2959-6386 (online), 2025)
This study explores the experiences, challenges, and aspirations of persons with disabilities in Mehendiganj, Barisal, Bangladesh. This study uses a qualitative approach, including in-depth, case-based interviews to gather detailed insights from a group of participants who were persons with disabilities. Key findings of this research show that people with disabilities in a particular region encounter significant barriers, including limited access to financial resources, inadequate access to education and vocational training, and a breakdown of society. A lack of infrastructure and support services exacerbates these challenges. Despite the challenges, the research reflects the core strengths and knowledge of the participants in different fields. Many of them strongly desire to overcome adversity and pursue aspirations of life through better education, employment opportunities, and social acceptance. The research also replicates the importance of the role of family support and social networks in reducing some of the difficulties faced by persons with disabilities. This research highlights the insistent need for comprehensive policies designed to address the unique needs of persons with disabilities. Recommendations include developing vocational and educational programs addressing the need, improving access to public services based on the requirements, and social awareness programs to combat discrimination and create social acceptance. This study will provide valuable insight for policymakers, social activists, and development professionals to create an inclusive and supportive environment for persons with disabilities in Bangladesh.